(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: The etiologies of mental disorders involve interactions among genetic, developmental, social, and environmental risk factors. An association between blood cadmium and depression was recently reported in young adults. Objective: To determine the prevalence of elevated blood cadmium level and to evaluate its association with depressive symptoms among adult Iraqi workers. Methods: A comparative cross-sectional study that conducted in two industries in Baghdad. It included 200 young adult male and female workers in the batteries factory (100 participants) who were exposed directly or indirectly to cadmium and in the textile factory (100 participants) unrelated to direct cadmium exposure. Blood sample was taken for measurement of blood cadmium level. Patient Health Questionnaire-9 was used to measure the symptoms of depression. Results: Mean of blood cadmium level was significantly higher in participants who had depressive symptoms than that in those who didn’t have; in those with moderate to severe symptoms than that in those who had mild symptoms. Blood cadmium >0.21 µg/dl is predictive for risk of development of depressive symptoms. Statistically significant weak positive correlations were detected between blood Cd with total PHQ9 score, no. of cigarettes/day, duration of work in batteries factory and in textile factory. Conclusion: Elevation of blood cadmium level among sample of adult Iraqi workers especially in batteries factory is a significant health problem. Cadmium neurotoxicity may be a contributing factor for adverse mental health outcomes, even at levels generally considered to pose low or no risk. Keywords: Depression, mental illness, health, cadmium, workers, Iraq Citation: Al-Samaraee MF, Sahib AAA. Blood cadmium level and its association with depressive symptoms in a sample of Iraqi workers. Iraqi JMS. 2022; 20(1): 44-50. doi: 10.22578/IJMS.20.1.6